Sexual Ethics and Islam: Feminist Reflections on Qur'an, Hadith, and Jurisprudence By Kecia Ali (Oxford, UK: Oneworld Publications, 2006. 217 pages.) (American Journal of Islam and Society, 2007)
Kecia Ali’s Sexual Ethics and Islam is a fresh and incisive examination of avariety of issues related to marriage and sexuality. Its primary objective is to engage with the values and aspirations of contemporary American Muslims,although it should also find a broad non-Muslim audience in undergraduatecourses and among non-specialist readers. Throughout the book, Ali analyzesthe concerns of a Muslim community striving both to realize a visionof justice and equality informed by contemporary social realities as well asto cultivate a genuine and honest commitment to Islam’s teachings.Although she sometimes addresses the internal dynamics of the Muslimcommunity (both American and international) in ways that may resonatemost with a faith-based audience, non-Muslim readers and students will befascinated by the degree of Muslim social and theological diversity that shedescribes.Ali identifies strongly with “progressive” Muslims, although she doesnot hesitate to critique liberal and conservative orthodoxies. She engagesintensively with an emerging canon of English-language progressiveIslamic thought, frequently citing such authors as Amina Wadud, AsmaBarlas, Khaled Abou El Fadl, Omid Safi, and Farid Esack. One of the book’sstriking (and useful) aspects is that it does not assume that the Islamic “center”lies in the Muslim-majority countries of the Middle East or South andSoutheast Asia; it unapologetically (and accurately) assumes that theMuslims of North America and other minority communities can produceautonomous and valid developments in Islamic thought and practice.Although her sympathies clearly lie with, for instance, those who wouldseek to accommodate the religious and personal aspirations of Muslim homosexuals(chapter 5), she also displays an unsparing commitment to internalconsistency and intellectual rigor. She neither resorts to easy platitudesabout Islam’s egalitarianism and justice nor tolerates them in the argumentsof others ...